2006
DOI: 10.1097/01.mpg.0000189328.47150.bc
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Crohn Disease in the Czech Republic in the Years 1990 to 2001 and Assessment of Pediatric Population with Inflammatory Bowel Disease

Abstract: This study confirmed an increase in incidence of CD in children younger than 15 years in the Czech Republic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 16 publications
5
40
4
Order By: Relevance
“…Prospective data from the USA confirm these findings [11]. The only pediatric studies from central and eastern Europe come from the Czech Republic and show an increasing incidence of CD among children (prospective study, 2000–2001) [12] and an increasing incidence of IBD among children 15 year of age and younger in Moravia, an eastern part of the Czech Republic (1990–2001) [13]. Our clinical observations in Poland permit similar conclusions of a stable increase in the number of newly diagnosed children with IBD.…”
Section: Introductionsupporting
confidence: 59%
“…Prospective data from the USA confirm these findings [11]. The only pediatric studies from central and eastern Europe come from the Czech Republic and show an increasing incidence of CD among children (prospective study, 2000–2001) [12] and an increasing incidence of IBD among children 15 year of age and younger in Moravia, an eastern part of the Czech Republic (1990–2001) [13]. Our clinical observations in Poland permit similar conclusions of a stable increase in the number of newly diagnosed children with IBD.…”
Section: Introductionsupporting
confidence: 59%
“…During follow-up, a trend for an increase in the incidence of CD was observed (from 2.1/10 5 to 2.6/10 5 ), while the incidence of UC remained unchanged (0.8/10 5 ). In Eastern Europe, Pozler et al [44] have recently published the results of a retrospective study investigating the incidence of CD in the Czech Republic in children diagnosed under the age of 15 years between 1990 and 2001. A marked increase in the incidence of CD was reported from 0.25/10 5 in 1990 to 1.25/10 5 in 2001.…”
Section: Most Of the Published Data Come From The Unitedmentioning
confidence: 99%
“…These studies however, have several limitations. Some of them were retrospective surveys [44] , while others were based solely on the in-and outpatient records of a single hospital, extrapolating the results to the investigated area [4] . Patients might have been unnoticed, thus the incidence rate is clearly underestimated.…”
Section: How Can We Explain the Recent Epidemiological Trends?mentioning
confidence: 99%
“…Recent research from several centers using appropriate laboratory methods showed that most people with chronic inflammation of the intestine of the Crohn's disease type are infected with this chronic enteric pathogen (2,9,53,63,66,67). Like that of Johne's disease, the incidence of Crohn's disease is increasing (43), particularly in children, with recent data from three sites in Northern and Central Europe and in Australia showing increases in the disease in children under 16 which average fivefold per decade (34,56,59).…”
mentioning
confidence: 99%